(3GdYhdeI hbVGjG GdGbJUGO GdSjGSjs - (3HOQj(B, (3jhfSs ((3HjQhJ(B:s (3OGQ GdaQGHj(B,s, 2000)
(3JQJcR gPg GdOQGSI Ydi GdfXQjGJ GdEbJUGOjI GdJj bOQ dgG Cf JQi GdfhQ aj MjR GdJWHjb hGdJj jOhQ MhdgG GdfbGT GdMGdj Hjf GdcJd GdYGdejI aj Mjf GffG feQ SQGYG Mhd GdfXQjGJ GdCNQi hgj GdacQ GdEbJUGOj cKjQI cKQI GdPjf JfGhdhG GdHMK Gdaj GdMbd ef Mbhd GdfTGW GdHTQj (B[......] (3gj eMGhdI Ydi VhA GdbhGYO GdHQGZeGJjI dQSe edGeM GdfXGe GdEbJUGOj GdPj jdGFe Mb GdEfSGf aj GdJeJY HeSJhi GLJeGYj eMJQe ddJJfejI aj LejY GdbWGYGJ GdEfJGLjI , hJhRjY GdKQhI GdhWfjI Hjf cd GdWHbGJ HMjK jJhaQ LRA ef aGFV GdbjeI dRjGOI GdJKeQ hJLOjO hSGFd GdEfJGL hJhRjY QbYI GdQCSedI GdbhejI (B. (3hYde GdEbJUGO EPG CMSf JWHjbg hJHfj GdJbfjGJ GdMOjKI bGO Ydi JMbjb Pdc(B.s
Keywords: (3GbJUGO SjGSjs; (3GdfXQjGJ GdEbJUGOjIs; (3YhdeIs